2021
DOI: 10.1016/j.ejc.2021.103331
|View full text |Cite
|
Sign up to set email alerts
|

Non-ambiguous trees: New results and generalisation

Abstract: We present a new definition of non-ambiguous trees (NATs) as labelled binary trees. We thus get a differential equation whose solution can be described combinatorially. This yields a new formula for the number of NATs. We also obtain q-versions of our formula. We finally generalise NATs to higher dimension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…They were put to light as a special case of tree-like tableaux, which have been found to have applications in the PASEP model of statistical mechanics [5,3]. The initial study of NATs revealed nice properties, mostly in an enumerative context [1,2]. This includes enumeration formulas with respect to fixed constraints (hook formula), and new bijective proofs of combinatorial identities.…”
Section: Introductionmentioning
confidence: 99%
“…They were put to light as a special case of tree-like tableaux, which have been found to have applications in the PASEP model of statistical mechanics [5,3]. The initial study of NATs revealed nice properties, mostly in an enumerative context [1,2]. This includes enumeration formulas with respect to fixed constraints (hook formula), and new bijective proofs of combinatorial identities.…”
Section: Introductionmentioning
confidence: 99%